Stand factors influencing Pinus halepensis decline in north‐western Spain. Issue 4 (12th January 2016) - Sanz‐Ros, A. V.; Valladares, F.; Diez, J. J.
Summary: Although decline of Aleppo pine was observed long ago and several climatic and biotic factors have been previously associated with this complex process, site factors involved in this decline remain poorly understood. The objective of the work described here was to identify site factors associated with canopy condition. Canopy condition was estimated both by a visual estimation of defoliation, and by an indirect estimation of leaf area index (LAI) and other stand‐ and light‐related parameters through the analysis of hemispherical photographs. A high percentage of damaged trees (81%) along with high levels of defoliation in plots (up to 53%) and trees (up to 85%) were recorded. Regression models showed that the site factors associated with defoliation were basal area, age, crown depth and elevation, while those associated with LAI were diameter at breast height, tree density and canopy openness. Analysis of hemispherical photographs proved to be a useful method for LAI estimation, but not for estimation of defoliation due to heterogeneous defoliation patterns caused by fungal pathogens detected in the study area. Soils and climatic conditions were common to all plots, so their influence could not be tested, but poor soil conditions and climatic restraints are known in this area, including low soil productivity, frequent summer droughts and high numbers of frost days. The results obtained suggest that several factors were associated with the decline of Pinus halepensis, including age, basal area, canopy openness, diameter, height and tree density. These factors can influence canopy condition, and thus, they might be acting as predisposing factors for the decline. The modulation of these factors is possible if suitable forest management strategies are applied, which could lead to a decrease of the decline incidence.